Gerontological nursing - Eliopoulos, Charlotte (Philadelphia, Pennsylvania : Wolters Kluwer, 2018)
Focusing on the content that students need to know for effective practice, this text offers engaging, evidence-based coverage of the aging process, factors contributing to healthy aging, and unique aspects of disease presentation and management in older adults.
Acute coronary syndromes in perspective / Melanie Humphreys -- Reducing the risk : primary care initiatives / Melanie Humphreys and Brenda Cottam -- Assessment of the cardiovascular system / Jackie Yonker -- Diagnosing acute coronary syndrome / John McGowan -- Unstable angina / John McGowan -- Non-ST segment elevation infarction / Melanie Humphreys -- ST segment elevation infarction / Claire Rushton -- Therapeutic intervention in acute coronary syndromes / Jan Keenan -- Cardiothoracic care / Debbie Danitsch -- Arrhythmias and their management / Melanie Humphreys and Celia Warlow -- Emergency cardiac care / Melanie Humphreys and Lisa Cooper -- Chronic cardiac conditions and their management / Ian Jones and Ann Dormer -- Cardiac rehabilitation / Tim Grove -- Secondary prevention within the community / Tim Grove -- Ethical issues in cardiac care / Pauline Walsh and Fiona Foxall
Includes index.
Keywords: GERIATIC NURSING